EXPLORING THE CORRELATION BETWEEN SELF-EFFICACY AND ORAL COMMUNICATION SKILLS AMONG SENIOR HIGH SCHOOL EFL STUDENTS IN INDONESIA - Jalu Wintang Widodo; Ali Mustofa; Syafi’ul Anam (Indonesian Journal of Learning and Instruction)
Oral communication has the important role in conducting English teaching and learning in this 21st century. By oral communication, the teachers can create the active learning atmosphere in the classroom. The major challenge that EFL senior high school faced active learning activity is the students’ anxiety in communication. This kind of problem has impact on their self-efficacy. This study aims to investigate the correlation of EFL senior high school students’ self-efficacy and their oral communication skills. There are 70 senior high school students who are involved in this research. The context of self-efficacy in this research is divided into two aspects, the level and sources of self-efficacy and its impact the students’ oral communication skill. The correlational study has been done by distributing close-ended questionnaire. The data were analyzed by Pearson Product Moment correlation. The research shows that there is significant correlation between EFL Senior High School Students’ Self-Efficacy and their Oral Communication Skills. It shown by the significance rate by that resulting more than 0.65. Moreover, the future research can involve more participants (more than 100 participants) in a wider scale.   Keywords: self-efficacy, EFL senior high school students, oral communication skill, correlation